Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/978-3-540-30136-3_62
|View full text |Cite
|
Sign up to set email alerts
|

Online Noninvasive Localization of Accessory Pathways in the EP Lab

Abstract: Abstract. Inverse electrocardiography has been developing during the last years and is about to become a valuable clinical tool for analyzing arrhythmias and electrical dysfunction in general. By combining measurements obtained by electrocardiographic body surface mapping with three-dimensional anatomical data, the electrical activation sequence of the individual human heart can be imaged noninvasively. This technique was applied on-line in the electrophysiology lab. The results of four patients, who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Geometrial regularization is achieved by a 2 nd order Tikhonov regularization applying the surface Laplacian. Studies confirmed that NICE can be applied in a clinical environment for solving electrophysiologically relevant problems (Berger T. et al, 2006;2011;Modre R. et al, 2004;2003;Seger M. et al, 2004;., Hanser F., Modre-Osprian R., Fischer G., Messnarz B., Berger T., Hintringer F., Pachinger O. & Roithinger F. X., 2002).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Geometrial regularization is achieved by a 2 nd order Tikhonov regularization applying the surface Laplacian. Studies confirmed that NICE can be applied in a clinical environment for solving electrophysiologically relevant problems (Berger T. et al, 2006;2011;Modre R. et al, 2004;2003;Seger M. et al, 2004;., Hanser F., Modre-Osprian R., Fischer G., Messnarz B., Berger T., Hintringer F., Pachinger O. & Roithinger F. X., 2002).…”
Section: Discussionmentioning
confidence: 80%
“…Selected publications reflecting the related development and progress of this method are (Berger T. et al, 2006;2011;Fischer G. et al, 2000;1999;Modre R. et al, 2006;2003;Pfeifer B. et al, 2008;Renhardt M. et al, 1992;Seger M. et al, 2004;Tilg B., Hanser F., Modre-Osprian R., Fischer G., Messnarz B., Berger T., Hintringer F., Pachinger O. & Roithinger F. X., 2002;Tilg B. et al, 1992;Wach P. et al, 2001;1997).…”
Section: General Description and Aim Of Nicementioning
confidence: 99%